Airway cells after swimming outdoors or in the sea in nonasthmatic athletes - Bonsignore, M. R.; Morici, G.; Riccobono, L.; Profita, M.; Bonanno, A.; Paterno, A.; Di Giorgi, R.; Chimenti, L.; Abate, P.; Mirabella, F.; Vignola, A. M.; Bonsignore, G. (Medicine & Science in Sports & Exercise, 2003)
BACKGROUND: Marathon runners and elite swimmers showed increased inflammatory cells in the airways at baseline. Although airway neutrophils increase further after a marathon race, the airway response to swimming is unknown. The aim of this study was to assess the effects of swimming on airway cells. To avoid the concomitant effects of chronic exposure to chlorine, the study was conducted in seven nonasthmatic swimmers [mean age (SD): 23.3 +/- 7.7 yr, training: 32 +/- 15 km.wk-1] habitually training in an outdoor pool (OP), i.e., a low-chlorine environment. METHODS: Spirometry, exhaled nitric oxide (NO), induced sputum, and peripheral blood samples were obtained at baseline, after a 5-km trial in OP, and after a 5-km race in the sea (S), i.e., hypertonic airway exposure. RESULTS: Airway neutrophil differential counts at baseline were higher in swimmers than in sedentary controls (N = 10), but cell counts, neutrophil elastase, and eosinophil cationic protein were unaffected by 5-km swimming. After swimming, L-selectin expression on airway cells decreased, suggesting exercise-induced cell mobilization into the airways and/or direct effects of hyperventilation on airway cells. After S, airway eosinophil differential counts increased slightly. Exhaled NO concentration was 19 +/- 6 ppb at baseline, 8 +/- 4 ppb after OP, and 21 +/- 7 ppb after S (P < 0.005 for OP vs baseline and S). CONCLUSIONS: In swimmers not chronically exposed to high chlorine concentrations, data obtained at baseline suggest a direct relationship between airway neutrophilia and endurance training. The low L-selectin expression by airway cells postexercise suggests hyperventilation-induced cell recruitment or modulation of cell function. Hypertonic exposure of airways during exercise may slightly increase airway eosinophils and exhaled NO. Overall, 5-km swimming exerted smaller effects on airway cells than running a marathon.